The Integration and Challenges of Traditional Folk Music and Modern Communication Technology - Wang, Xiaolin; Ariunaa (International Journal of Social Sciences and Public Administration, 2024)
In today's increasingly advanced science and technology, digital technology is having a profound impact on traditional folk music due to its great influence and wide application. As a pearl in China's culture, traditional folk music carries rich historical connotation and national characteristics. Moreover, under the driving force of digital technology, there are obvious changes in the dissemination method, creation method and expression form of traditional folk music. The article aims to discuss the impact of digital technology on traditional folk music, analyse the opportunities and challenges, and then put forward coping strategies to promote the inheritance and development of traditional folk music in China.